Capins marandu, decumbens e convert submetidos à adubação nitrogenada - Cabral, Carlos Eduardo Avelino (2011)
The hybrid convert grass is formed from forage requirements of different soil fertility, and therefore, comparative studies are needed with other grasses to able its proper fertilizer recommendation Thus, the objective was to compare the characteristics of productive, morphological and nutritional of Marandu, Signal and Convert grasses submitted to nitrogen fertilization. The experiment was conducted in a greenhouse at Universidade Federal de Mato Grosso, Rondonopolis Campus. The experimental design was completely randomized design with fifteen treatments and four replications arranged in a 3x5 factorial, with three grasses and five doses of nitrogen. The species forages were: Brachiaria brizantha cv. Marandu (marandu grass), Brachiaria decumbens cv. Basilisk (signal grass) and Brachiaria hibrida CIAT 36087 (convert grass), subjected to nitrogen levels of 0; 100; 200; 300 and 400 mg dm-3. Each plot consisted in pots 5 dm-3 with five plants. The humidity was maintained at field capacity by means of tensiometers. Were realized three cuts to 10 cm at intervals of 30 days. Productive characteristics were evaluated: shoot dry mass, root dry mass, relationship between them, nitrogen use efficiency for the production of shoots, leaf and stem; morphology: leaf and stem dry mass; structural: height, ratio leaf/stem, number of leaves and tillers, nutritional: SPAD reading, concentration of nitrogen shoot, leaf, stem and roots. The maximum production of shoots and leaves of the convert grass nitrogen levels occur intermediate to the other grasses. In the first and second cut grass convert produces greater dry mass of leaves. The signal grass produces higher dry mass of stem, number of leaves and tillers. Convert and signal grasses produces greater dry mass of roots. The highest concentration of nitrogen in the shoot and the leaf and stem fractions sheath occurs in grasses Marandu and Convert. There are more efficient use of nitrogen for the production of shoots in Signal and Convert grasses. SPAD readings greater than 26 indicate that the grasses are Marandu and Convert with adequate 11 concentration of nitrogen. The grass-convert can be alternative production systems in low to medium technological level.